Influence of traffic context and information presentation on evaluation of autonomous highway journeys. (October 2021) - Ritchie, Owain T.; Watson, Derrick G.; Griffiths, Nathan; Xu, Zhou; Mouzakitis, Alex
Highlights: Rule-based autonomous vehicles (AVs) could face 'bullying' from human drivers. Journey satisfaction has received less attention than trust regarding AVs. We investigated effects of speed, lane position and information on satisfaction. Being overtaken reduced satisfaction even when travelling at the speed limit. Information presentation had limited effects on occupants' satisfaction levels. The results have implications for integrating AVs into traffic. Abstract: Previous research into perceptions of autonomous vehicles has largely focused on a priori attitudes, with little work on the perception of specific traffic situations, context and driving styles. The present study used three simulator experiments (total N = 150) to examine the combined effects of vehicle speed, lane position, information presentation and traffic context on occupants' levels of satisfaction with autonomous highway journeys. Overall, occupants preferred being in a vehicle that was mostly overtaking compared to being overtaken, regardless of whether the overtaking vehicles were exceeding the speed limit. This finding remained even when occupants were given additional reminders that they themselves were travelling at an appropriate speed (Experiments 1 & 2). Experiment 3 found that occupants preferred overtaking to being overtaken when following another car, but this preference disappeared when they were following a lorry, suggesting that occupants' sensitivity to position amongst the traffic was partially context dependent. Overall, the findings suggest that journey satisfaction is sensitive to overtaking contexts and the inappropriate behaviour of other drivers (e.g., speeding) can reduce journey satisfaction for occupants in autonomous vehicles that drive within the speed limit, depending on the specific traffic situation. Potential implications for the integration of autonomous vehicles with other traffic and the need for in-vehicle presentation of information are discussed.